Optimism gone bad? The persistent effects of traumatic experiences on investment decisions - Chi Hyun Kim (Humboldt University Berlin, 2021)
Do memories of highly emotional stock market crashes permanently affect the investment decisions of households? The Initial Public Offerings of Deutsche Telekom during 1996- 2000 provide an optimal base to address this question, as it is known for its emotional character and is reputedly "the last time Germans invested in stocks." Using Socio-Economic Panel (SOEP) household survey data, I show that having experienced this event leads to persistently lower stock market participation in the future. In addition, this effect is greater for households that had directly invested in Telekom shares, those being more likely to have high emotional experiences. Finally, I also show that such traumatic experiences on investment decisions have intergenerational consequences, significantly affecting how the next generation invests in the financial market.
urn:nbn:de:kobv:11-110-18452/23880-8
Keywords: D14; G01; G11; E21; 330; Household finance; stock market participation; financial crises